Travelling between journalism and literature: kipling’s art in crossing fixed textual borders - Simões-Ferreira, Isabel (2017)
The paper explores Kipling’s art and craftsmanship as a storyteller, whether one is talking about real/factual news reporting or imaginary stories. The main focus falls on Kipling’s experience both as a journalist and a writer in order to problematize the blurring line that sometimes divides these two genres of narrative regarding their commitment to telling the truth. Three texts were chosen for this purpose: “The Sutlej Bridge”, a news article published by the Civil and Military Gazette (1887); and two tales “The Man Who Would Be King” (Wee Willie Winkie, 1888) and “The Bridge Builders” (The Day’s Work, 1898). From a thematic perspective, these narratives are linked, on the one hand, by the act of construction — the construction of bridges or empire-building — and, on the other hand, by the role of the journalist in reporting what he sees and/or listens to. The analysis demonstrates that fiction/literature can often supersede in scope and depthness factual accounts of reality, thus aiming to reach higher levels of truthfulness.